Google Sites-Based Interactive Multimedia to Improve Social Studies Learning Outcomes for Fourth-Grade Elementary School Students - Arita Marini , Desy Safitri , Gusti Yarmi , Syafrili Ardina Mutiara (South Eastern European Journal of Public Health, 2025)
This study investigated the impact of Google Sites-based interactive multimedia on enhancing learning outcomes in social studies among elementary school students. Employing the research and development (R&D) method, the study followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research adopted a one-group pretest-posttest design, where a single sample group underwent treatment, with their performance evaluated before and after the intervention. The population was elementary school students in the Cakung sub-district, East Jakarta, Indonesia. Using the Slovin formula, a random sample of 32 fourth-grade students was selected as the practical group. Hypothesis testing was conducted using a t-test through SPSS 29, which revealed a statistically significant improvement in learning outcomes, with both one-tailed and two-tailed p-values recorded at less than 0.001. These findings demonstrate that Google Sites-based interactive multimedia effectively enhances social studies learning outcomes for fourth-grade students in the Cakung sub-district, East Jakarta, Indonesia.